Model Kirkpatrick dalam Evaluasi Program Sosialisasi Pembinaan Aparatur Sipil Negara (Asn) Kantor Kementerian Agama Kabupaten Mamasa - Ramli L; Rasyid, Muhammad Nur Akbar; Mania, Sitti (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to describe the evaluation of the socialization program for ASN coaching at the Office of the Ministry of Religion of Mamasa Regency. This research method is qualitative research, information or data is collected using interview instruments, observations and document studies. This study also aims to measure, the extent to which this program is beneficial to the socialization participants and the good impact on the agency, therefore, to find out that the researcher uses the Kirkpatrick evaluation model using 3 levels: Level 1-Reaction, Level 2-Learning, and Level 3-Behavior. The evaluation began by measuring the participants' reaction to the socialization carried out, then continued by measuring the improvement of their knowledge and skills after participating in the program, furthermore, this study identified the behavioral changes that occurred among ASN as a result of the coaching. The results of this study show that the socialization program for ASN coaching at the Ministry of Religion Mamasa Office has succeeded in having a positive impact, both in terms of knowledge, behavior change, and contribution to improving ASN performance. These findings provide recommendations for the development of similar programs in the future with an emphasis on behavioral and performance aspects in the workplace.